Periprosthetic joint infection with streptococcus dysgalactiae subspecies equisimilis: Case report - ERDEN, TUNAY; Erden, Tunay; SÜMBÜL, BİLGE; Gultepe, Bilge Sumbul; KÜÇÜKDURMAZ, FATİH (My University, 2020)
Streptococcus dysgalactiae (SD) is a common pathogen among elderly population. However, to our knowledge, there is no periprosthetic joint infection case reported that is infected with Streptococcus dysgalactiae subspecies equisimilis (SDSE) in the English literature. In this article, we report a 77 -year -old male patient who had undergone total knee arthroplasty three years ago and had the diagnosis of cellulitis at his leg followed by swelling, pain and hyperemia localized at his knee. Three knee aspirations were performed and the SDSE was identified. There was no direct contact of patient to animals.